Epic Stone Butch transmasculinity in the work of Willa Cather - Hammer, K. Allison (Transgender Studies Quarterly, 2020)
Through application of the contemporary term transmasculinity and the more historical stone butch, the author questions the critical tendency to perceive American writer Willa Cather only as lesbian while ignoring or undertheorizing a transgender longing at play in her fiction, short stories, and letters. While biographical evidence must not be approached as simply coterminous with literary production, as literature often exceeds or resists such alignments, Cather's letters in particular suggest a strong identification with her male fictional alliances. Analysis of her letters alongside two of her most treasured, and disparaged, novels, One of Ours (1922) and The Professor's House (1925), conveys Cather's wish for an idealized masculinity, both for herself and for Western culture, that would survive two coeval historical processes and events: the closing of the American frontier and the First World War. Through what the author calls a stone butch “armature,” she and her characters retained masculine dignity despite historical foreclosure of Cather's manly ideal, Winston Churchill's Great Man, who was for her the artistic and intellectual casualty of the period. Cather expressed the peculiar nostalgic longing present in stone butch, and in the explosion of new forms of transmasculinity in the present. This suggests that historical transgender styles don't disappear entirely, even as new categories emerge.
Keywords: 1900-1999; 1910-1919; 1920-1929; amériques; approches et analyses; arts; butch; discipline; identités LGBTQIA2+; personnes trans*; périodes historiques; queer; régions géographiques; états-unis; études littéraires

Les archipelles. Célébration poético-critique des littératures lesbiennes québécoises (1975-1992) - Maréchal, Maël (Lettres québécoises, 2020)
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; amériques; approches et analyses; arts; discipline; littérature québécoise; personnes lesbiennes; périodes historiques; queer; québec; ressource en ligne; régions géographiques; études littéraires